INNV-13. ALLELE: A CONSORTIUM FOR PROSPECTIVE GENOMICS AND FUNCTIONAL DIAGNOSTICS TO GUIDE PATIENT CARE AND TRIAL ANALYSIS IN NEWLY-DIAGNOSED GLIOBLASTOMA. (5th November 2018) - Touat, Mehdi; Dubuc, Adrian; Meredith, David; Tsuji, Junko; Mills, Caitlin; Gaffey, Sarah; Geduldig, Jack; Watkinson, Fiona; Pelton, Kristine; Malinowski, Seth; Lennon, Niall; Sorger, Peter; et al.
Abstract: BACKGROUND: Advances in genomic profiling, together with a better understanding of cancer genetic drivers have generated opportunities for precision medicine trials in newly diagnosed glioblastoma (GBM). ALLELE is a consortium to create independent infrastructure for prospective genomics and functional diagnostics to support biomarker-driven trials in GBM. METHODS: Multi-center prospective study of molecular profiling in newly diagnosed GBM. Clinical (CLIA) tumor/normal whole exome sequencing (WES) and genome-wide copy number array (CNA) were performed. Primary objective: to evaluate the feasibility of genotyping tumors with a turnaround time allowing prospective data use in prospective trials. Secondary objectives included developing infrastructure for novel functional biomarker assays and investigating the clinical yield of tumor/normal WES and CNA in GBM. RESULTS: As of 5/1/18, 65 patients with GBM enrolled among 7 sites. Median age was 59. WES and CMA were completed in 60 patients, with a median time between tissue submission and reporting of 22 days (range 15–35). 33 patients were enrolled in INSIGhT, a randomized platform adaptive trial comparing standard of care versus adjuvant CC-115, neratinib or abemaciclib in MGMT unmethylated newly diagnosed GBM (NCT02977780). In each arm, pre-defined biomarkers (EGFR, PI3K and CDK) will be evaluated for their ability to predict outcome. Potentially actionable findings were identified in 30 patients, and included EGFR amplification, mutations of BRAF, FGFR1, IDH1/2 or FGFR3 or MET fusion. Four tumors were reclassified based on genomics. Functional biomarker assays were developed for real-time evaluation of pharmacodynamic responses in ex vivo models. Updated results of exploratory biomarker analyses will be presented at the conference. CONCLUSIONS: Real-time WES, copy number arrays and functional diagnostics are feasible in newly diagnosed glioblastoma, and can support a variety of biomarker-driven trials. Genomic analyses conducted in a prospective manner can inform subsequent clinical trial analysis aiming at matching outcome with tumor genotyping.